The Influence Of Liquidity, Leverage , Profitability, And Inflation On Stock Prices: Case Study of Trading Companies on the Indonesian Stock Exchange for the 2017 – 2021 Period - Supriadi, Yoyon; Standika, Christian; Nurisnaini, Neni (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to examine the influence of liquidity, Leverage, profitability, and inflation on the stock prices of trading companies listed on the Indonesia Stock Exchange during the period of 2017-2021. A quantitative approach was utilized in this study. The sample was selected using purposive sampling method, consisting of trading companies listed on the Indonesia Stock Exchange during the years 2017-2021. Initially, there were 79 companies, but the sample was narrowed down to 8 trading companies where their financial reports were publicly available and accessible. The findings of this study are as follows: (1) Current Ratio (CR) does not have a significant impact on stock prices, with a significant value of 0.365 > 0.05. (2) Debt to Equity Ratio (DER) does not have a significant impact on stock prices, with a significant value of 0.320 < 0.05. (3) Return on Equity Assets (ROA) has a significant positive influence on stock prices, with a significance value of 0.00 < 0.05. Based on the simultaneous testing results, this research confirms a significant influence between the variables of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on Stock Prices, with a significant value of 0.000 < 0 . Keywords: Liquidity, Leverage, Profitability, Inflation, Stock Prices.